Research progress of exosomes in drug resistance of breast cancer - Liu, Lihui; Jiang, Daqing; Bai, Shi; Zhang, Xinfeng; Kang, Yue (Frontiers in Bioengineering and Biotechnology, 2024)
Since breast cancer is such a heterogeneous disease, an extensive variety of treatments are currently available, including chemotherapy, endocrine therapy, targeted therapy, immunotherapy, radiation therapy, and others. Even though there are numerous treatment options, breast cancer recurrence, and metastasis pose a significant threat to patient survival and present a challenging clinical problem. Exosomes, a carrier of cell-to-cell communication in the tumor microenvironment, are very special and significant in the therapy of breast cancer medication resistance. More and more clinical research has shown in recent years that there are numerous connections between exosomes and breast cancer therapy resistance. The progress exosomes have made in the treatment of breast cancer drug resistance is reviewed in this paper, which also offers a theoretical framework for investigating fresh approaches to combating breast cancer drug resistance.